A lignin-based carbon aerogel enhanced by graphene oxide and application in oil/water separation. (15th October 2020) - Meng, Yi; Liu, Tanglong; Yu, Shanshan; Cheng, Yi; Lu, Jie; Wang, Haisong
Graphical abstract: Highlights: A lignin-based carbon aerogel enhanced by graphene oxide (LCAGO) is fabricated. Aminated lignin and GO enhance the gel's mechanical property synergistically. Annealed temperature of the carbonated gel can drop as low as 350 ℃. Annealed sample showed super-hydrophobicity with a water contact angle of 150°. The prepared sample has good oil–water separation effect. Abstract: A lignin-based carbon aerogel enhanced by graphene oxide (LCAGO) is fabricated. As the strong reaction between amine groups from lignin derivates and carboxylic groups from GO and acrylic acid (AA), the compactness and the cross-linkage of the gel are much higher than the samples without lignin derivate and GO. The lignin derivates are used as cross-linkers and GO contributes to reach to superhydrophobicity with a low annealing temperature and improves the mechanical performance after annealing. The carbon aerogel achieves a water contact angle of 150° at 350 °C for 2 h, achieving the energy-saving purpose. The synergistic effect of superhydrophobicity and good mechanical property acquired by lignin derivate and GO ensures the carbon aerogel appropriate for oil/water separation and light oil, heavy oil and emulsified oil are separated respectively by the gel. The oil adsorption ratio is about 32–34 g/g and shows a moderate performance, which is compared with the reported biomass-based materials. The results indicate the material is a highly effective and practicable water-cleaning material. The preparation process is energy-saving and is a pathway for separation and collection oil from water with industry waste.